2021
DOI: 10.3390/jcs5030076
|View full text |Cite
|
Sign up to set email alerts
|

S-N Curve Characterisation for Composite Materials and Prediction of Remaining Fatigue Life Using Damage Function

Abstract: S-N curve characterisation and prediction of remaining fatigue life are studied using polyethylene terephthalate glycol-modified (PETG). A new simple method for finding a data point at the lowest number of cycles for the Kim and Zhang S-N curve model is proposed to avoid the arbitrary choice of loading rate for tensile testing. It was demonstrated that the arbitrary choice of loading rate may likely lead to an erroneous characterisation for the prediction of the remaining fatigue life. The previously proposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…Kim and Huang [8] confirmed and verified a method for predicting the RFL with a new method for S-N curve characterisation applicable for time dependent materials, using the fatigue damage as a function of two independent variables at a single stress ratio (R) under tension-tension loading. As a natural progression, the prediction of the RFL using the fatigue damage as a function of three independent variables has been desired.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Kim and Huang [8] confirmed and verified a method for predicting the RFL with a new method for S-N curve characterisation applicable for time dependent materials, using the fatigue damage as a function of two independent variables at a single stress ratio (R) under tension-tension loading. As a natural progression, the prediction of the RFL using the fatigue damage as a function of three independent variables has been desired.…”
Section: Introductionmentioning
confidence: 85%
“…In fact, the breaking point is usually not obtainable from a fatigue testing machine because of the limited controllability, but it can be obtained from a universal testing machine. A practical method for using the value of 0.5 is proposed for time-dependent materials applicable to metallic materials [8].…”
Section: The Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…The classification societies' rules prescribe the procedure for obtaining S-N curves for composite materials. Various authors have reported results obtained in modeling S-N curves for composites [29,34,35] and the prediction of the fatigue life of composite structures [27,43,44]. A failure model for groups of similar glass/polyester composites, such as the ones used in this research, can be defined in the form:…”
Section: Structural Durability Assessmentmentioning
confidence: 99%
“…Indeed, a large experimental library can be found in the literature regarding fatigue testing of UD or cross-ply laminates, in which mainly uniaxial stress states are developed [3][4][5][6][7][8][9][10][11]. The damage response of [45 • /−45 • ] laminates during fatigue has been also investigated [12,13].…”
Section: Introductionmentioning
confidence: 99%